2016
DOI: 10.1097/ccm.0000000000001437
|View full text |Cite
|
Sign up to set email alerts
|

Saving Patients’ Lives Through Activating a Rapid Response System

Abstract: Commission, it has gained wide acceptance and has been implemented across many hospitals. However, despite the clear clinical intuition underlying the RRS concept and its popularity, several studies have failed to show a significant improvement in patient outcomes, in particular, in reduced patient mortality (2). Such results have led to controversy regarding its effectiveness. The RRS concept is a hospital-wide intervention with the intention and promise to save patient lives. However, among the 10 patient sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Importantly, we found that nighttime RRT activation was associated with prolonged latency from the onset of concerning symptoms and signs. Delays in RRT activation have been shown to be associated with worse outcomes [ 35 , 36 ]. These increased delays may occur because of impaired recognition and/or monitoring of clinical deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we found that nighttime RRT activation was associated with prolonged latency from the onset of concerning symptoms and signs. Delays in RRT activation have been shown to be associated with worse outcomes [ 35 , 36 ]. These increased delays may occur because of impaired recognition and/or monitoring of clinical deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Delays in RRT activation have been shown to be associated with worse outcomes. 25,26 It is unclear why these delays occurred. It may be that these patients were less ill appearing or frail (a higher proportion were initially from home, as opposed to a long-term care facility), and therefore, there was delay to activation of the RRT.…”
Section: Discussionmentioning
confidence: 99%